Modulation of electrical activity of proteinoid microspheres with chondroitin sulfate clusters. - Panagiotis Mougkogiannis; Andrew Adamatzky (PLoS ONE)
Proteinoids-thermal proteins-are produced by heating amino acids to their melting point and initiation of polymerisation to produce polymeric chains. Proteinoids swell in aqueous solution into hollow microspheres. The proteinoid microspheres produce endogenous burst of electrical potential spikes and change patterns of their electrical activity in response to illumination. These microspheres were proposed as proto-neurons in 1950s. To evaluate pathways of potential evolution of these proto-neurons and their applicability of chimera neuromorphic circuits we decided to hybridise them with hondroitin sulphate (CS) clusters, which form a part of the brain extracellular matrix. We found a novel synergistic interaction between CS clusters and proteinoids that dramatically affects patterns of electrical activity of proteinoid microspheres. Our study might shed light on evolution of synaptic plasticity's molecular mechanisms and the role of extracellular matrix-protein interactions in learning, and open up possibilities for novel methods in unconventional computing and the development of adaptable, brain-inspired computational systems.